Comparison of clinical characteristics and treatment efficacy in childhood‐onset schizophrenia and adolescent‐onset schizophrenia in mainland China: A retrospective study. Issue 6 (19th January 2021) - Cheng, Xin; Zhang, Huihui; Zhang, Jiuping; Xu, Ping; Jin, Peiying; Fang, Hui; Chu, Kangkang; Ke, Xiaoyan
Abstract: Aim: The comparative study of childhood‐onset schizophrenia (COS) and adolescent‐onset schizophrenia (AOS) is scarce. This study aimed to examine the differences in clinical presentations and treatment efficacy between COS and AOS and further analyse the factors affecting the efficacy of early‐onset schizophrenia (EOS). Methods: A total of 582 electronic medical records of inpatients with EOS (216 COS and 366 AOS inpatients) between 2012 and 2019 were retrospectively analysed. The positive and negative syndrome scale (PANSS) was used to assess psychotic symptoms. Logistic regression analysis was performed to analyse the predictors of efficacy. Results: The mean age of onset of EOS was 12.87 ± 2.19 years. The importance of better diagnosing COS appeared in a longer illness course, more frequently insidious onset, less frequent delusions, more severe negative symptoms and bizarre behaviours than AOS. Besides, COS had more frequent visual hallucinations and impulsive behaviours than AOS. After hospitalization, the improvement rate of psychotic symptoms in COS and AOS were 38.3% and 47.8%, respectively. The difference of efficacy between the two groups was statistically significant. Days of hospitalization, age of onset, presence of flat affect, PANSS total and negative score at admission were predictors of treatment efficacy in EOS individuals. Conclusions: COS inpatients suffer more obvious negative symptoms, bizarre behaviours, visual hallucinations and impulsive behaviours and worse efficacy than AOS inpatients. The severity of negative symptoms and age of onset seem the most noteworthy predictors of efficacy. These findings highlight the importance of early detection and early intervention.